BECN2 (beclin 2)-mediated non-canonical autophagy in innate immune signaling and tumor development. Issue 12 (1st December 2020) - Zhu, Motao; Deng, Guangtong; Xing, Changsheng; Nie, Guangjun; Wang, Rong-Fu
ABSTRACT: BECN2 (beclin 2) is a newly identified mammalian-specific macroautophagy/autophagy family member, and plays a critical role in the control of obesity and insulin sensitivity. However, its role in innate immune signaling and inflammation remains elusive. In our recent study, we show that BECN2 functions as a negative regulator in innate immune signaling and tumor development through non-canonical autophagy. Loss of Becn2 causes splenomegaly, lymphadenopathy, elevated proinflammatory cytokine production and spontaneous lymphoma development in mice. Mechanistically, BECN2 mediates the degradation of MAP3K7/TAK1 and MAP3K3/MEKK3 through an ATG9A- and ULK1-dependent but ATG16L1-BECN1-MAP1LC3B/LC3B-independent autophagy pathway to control systemic inflammation. BECN2 interacts with MAP3K7 and MAP3K3 through the engagement of ATG9A + vesicles upon ULK1 activation, and promotes the fusion of MAP3K3- or MAP3K7-associated ATG9A + vesicles with phagophores for subsequent degradation. Our findings have identified a previously unrecognized role of BECN2 in innate immune signaling and tumor development through non-canonical autophagy, thus providing a potential target for inflammatory disease and cancer therapy.